MEASUREMENT OF SERVICES QUALITY IN OUTPATIENT PHARMACY UNIT AT GENERAL REGIONAL HOSPITAL SLEMAN - Rizkia Ainaini; Marchaban Marchaban; Triana Hertiani (Faculty of Pharmacy, Universitas Gadjah Mada)
Health service facilities which are considered to have an excellency will also have a greater opportunity tobe selected by the customer. The formation of positive perceptions from customer that is expected to bringsatisfaction will provide a positive impact on efforts to increase profit and service in Hospital Pharmacy Unit. Thisstudy was aimed to measure the services quality in Outpatients Pharmacy Unit at Regional General Hospital Slemanwhich were reviewed from input, process, and outcome variables.The input variables were assessed through observation of the pharmacy services supporting resources,interviews with the insurer Pharmacists unit responsible for outpatient and job satisfaction questionnaires ofOutpatient Pharmacy Unit employees. The variable process was assessed through the results of drug use indicators.The variable outcome was assessed through value gap customer satisfaction questionnaires based on SERVQUAL methods. Subjects in the study covered the pharmacy services supporting resources (9 persons of employee), prescription drugs, and customers of Outpatient Pharmacy Unit at General Hospital Sleman (257 prescription drugs and customers). Input variables data were analyzed by descriptive analysis. Process variables data were checkedfor completeness from its data fields, tabulated and analyzed using a triangulation method. Outcome variables datawere analyzed by gap analysis.Results showed that the outcome of service did not match the quality services target of Pharmacy Unit at General Regional Hospital Sleman. The gap values of all dimensions service quality were negative, outpatient customers satisfaction index score was 74.41%. Some of the resources input variables need improvement and have not fulfilledthe Law on Hospitals, Government Regulation on Pharmacy Practice, Standard for Pharmacy Services in Hospital, aswell as there were still some obstacle on process variables that affect the pharmacyservices. Key words: pharmacy services quality, the variable input, process, outcome,Outpatient Pharmacy Unit GeneralHospital Sleman.